2013
DOI: 10.1016/j.jneumeth.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser deinsulation of Parylene-C on iridium for use in an activated iridium oxide film-coated Utah electrode array

Abstract: Implantable microelectrodes provide a measure to electrically stimulate neurons in the brain and spinal cord and record their electrophysiological activity. A material with a high charge capacity such as activated or sputter-deposited iridium oxide film (AIROF or SIROF) is used as an interface. The Utah electrode array (UEA) uses SIROF for its interface material with neural tissue and oxygen plasma etching (OPE) with an aluminium foil mask to expose the active area, where the interface between the electrode an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…Laser ablation has been used previously to selectively remove parylene-C from electrode tips of the UTAH (Blackrock Microsystems) neural recording array. [42] In that instance, the electrodes themselves remained intact following laser treatment. Using LCGO fibres as the electrode material, low laser powers (230-250 mW) cut through both the coating and the fibre.…”
Section: Electrode Fabricationmentioning
confidence: 97%
“…Laser ablation has been used previously to selectively remove parylene-C from electrode tips of the UTAH (Blackrock Microsystems) neural recording array. [42] In that instance, the electrodes themselves remained intact following laser treatment. Using LCGO fibres as the electrode material, low laser powers (230-250 mW) cut through both the coating and the fibre.…”
Section: Electrode Fabricationmentioning
confidence: 97%
“…Due to platinum and gold’s faradaic nature, their limitations of charge delivery capacity remain a great challenge, especially for the electrodes with small geometric surface areas. With weak or no faradaic reaction charge transduction, the contribution of double-layer capacitive coupling in charge delivery is often limited [ 83 ]. Thus, materials with higher electroactivity and ability to support reversible faradaic reactions are needed to promote the charge transfer in the electrode–tissue interface.…”
Section: Metals and Their Derivativesmentioning
confidence: 99%
“…Carbon nanomaterials achieve this mainly by increasing the electrochemical surface area (ESA), whereas PEDOT–PSS and IrO x introduce a dominant faradaic charge transfer mechanism. However, premature delamination and cracking during prolonged studies as well as large variability between samples has been reported repeatedly in the literature. , A widely accepted electrode material for chronic recording and stimulation applications in implantable devices is iridium oxide films: either sputtered iridium oxide films (SIROF) or activated iridium oxide films (AIROF). Cogan et al have studied the properties of AIROF and SIROF in detail by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). AIROF electrodes are fabricated on iridium metal by cyclic oxidation and reduction of the metal surface after the electrode array has been fabricated.…”
Section: Introductionmentioning
confidence: 99%